2018
DOI: 10.7150/jca.27475
|View full text |Cite
|
Sign up to set email alerts
|

Tumor deposit is an independent prognostic indicator in patients who underwent radical resection for colorectal cancer

Abstract: Background: Tumor deposits are one of the promising factors among the different edition of Tumor, Node, Metastasis classification. Despite improvement in the treatment of various types of metastatic disease the source and prognostic significance of tumor deposits in staging has not been deliberating the agreeable opinion. We investigated the possibility of tumor deposit as independent prognostic factor and evaluating its prognostic value in colorectal carcinoma patients.Methods: Author studied 313 colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Mayo et al [16] showed that TDs were associated with worse 3-year OS overall survival in patients of any known and unknown N categories, which suggested that TDs might be associated with a risk of all-cause death or cancer-specific death at least similar to a positive lymph node in all N categories. Basnet et al [17] signified that TD was an independent prognostic factor associated with metastatic diseases along with vascular invasion and the number of metastatic lymph nodes among CRC patients. All these studies indicated that it might be more reasonable to differentiate prognostic significance of TD status from that of metastatic lymph nodes [18], and more details of TDs should be explored in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mayo et al [16] showed that TDs were associated with worse 3-year OS overall survival in patients of any known and unknown N categories, which suggested that TDs might be associated with a risk of all-cause death or cancer-specific death at least similar to a positive lymph node in all N categories. Basnet et al [17] signified that TD was an independent prognostic factor associated with metastatic diseases along with vascular invasion and the number of metastatic lymph nodes among CRC patients. All these studies indicated that it might be more reasonable to differentiate prognostic significance of TD status from that of metastatic lymph nodes [18], and more details of TDs should be explored in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear how to classify TDs in the TNM classification. Some researchers have suggested that TDs should be counted as positive LNs, and that this may be superior to the (25). These findings suggest that TDs may differ from positive LNs and may have specific prognostic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Basnet et al. demonstrated that TDs were not equivalent to positive LNs, but did not provide detailed information about the exact role of TDs ( 25 ). These findings suggest that TDs may differ from positive LNs and may have specific prognostic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…2 Colorectal cancer is the third leading cause of morbidity and mortality in both men and women. 3 With the improvement in living standards and changes in diet, the incidence of colorectal cancer continues to rise. 4 The treatment of colorectal cancer includes surgery, chemotherapy, radiotherapy and other biological immunological treatments.…”
Section: Introductionmentioning
confidence: 99%